2008
DOI: 10.1515/znb-2008-0630
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a Piezotolerant Mutant of Lactobacillus sanfranciscensis

Abstract: Incubation under sublethal high pressure (50 MPa) allowed the isolation of a piezotolerant mutant of Lactobacillus sanfranciscensis. Compared to the wild type this strain showed faster growth at 50 MPa and an altered temperature-dependent growth at ambient pressure. Additionally, an altered antibiotic resistance pattern was detected. To address the molecular basis of the mutation the genotypic characterisation was focused on alterations of ribosomal components. Northern analysis using ssrA (transfer mRNA) as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In contrast, because no fermentation occurred at 100 MPa (with no adaptation to pressure), there was no need for re-adaptation upon the return to atmospheric pressure. Several authors previously reported that microbial cultures subjected to HHP shocks (successive rounds of increasing pressure) acquire resistance to subsequent HHP treatments due to the development of adaptation mechanisms [23][24][25][26][27][28]. Adaptation is usually associated with the induction of a large number of genes, the synthesis of stress response proteins and the development of cross-resistance to a variety of stresses [29][30][31][32].…”
Section: Inhibition Of Fermentation At Hhp and Subsequent Occurrence mentioning
confidence: 99%
“…In contrast, because no fermentation occurred at 100 MPa (with no adaptation to pressure), there was no need for re-adaptation upon the return to atmospheric pressure. Several authors previously reported that microbial cultures subjected to HHP shocks (successive rounds of increasing pressure) acquire resistance to subsequent HHP treatments due to the development of adaptation mechanisms [23][24][25][26][27][28]. Adaptation is usually associated with the induction of a large number of genes, the synthesis of stress response proteins and the development of cross-resistance to a variety of stresses [29][30][31][32].…”
Section: Inhibition Of Fermentation At Hhp and Subsequent Occurrence mentioning
confidence: 99%
“…E. coli and Lactobacillus sanfranciscensis have shown to primarily respond to sublethal HHP shock by strong upregulation of rRNA genes, ribosomal proteins, and translation-associated proteins [38][39]. Moreover, growing of L. sanfranciscensis at 50 MPa for 25 generations allowed for the isolation of a mutant strain with enhanced ability to grow under pressure and cross-resistance to ribosome-targeting antibiotics, which presented upregulated expression of SsrA in comparison to its parent [40]. SsrA (also known as tmRNA) is a small, highlystructured RNA that controls protein synthesis and recycles stalled ribosomes [41], and disruption of the ssrA gene impaired growth (50 MPa) and even survival (300 MPa) under pressure [40].…”
Section: Adaptation Of Mesophilic Bacteria To Sublethal Hhpmentioning
confidence: 99%
“…It is possible to decrease the stability of these microorganisms if the lower temperatures are applied during high pressure treatments (Buckow, Heinz, 2008). However, there are an increasing number of mesophilic microorganisms with achieved significant improvement of growth under high pressure or resistance to high pressure directed by evolution (Hauben et al, 1997;Karatzas, Bennik, 2002;Pavlovic et al, 2008;Aertsen et al, 2009). Ability to resist pressure treatment varies considerably among different microorganisms' type, form (vegetative cells or spores, Gram-positive or Gram negative), genus, species, and strain.…”
Section: Microbiological Aspectsmentioning
confidence: 99%